Finite Element Method: An Overview - JAGOTA, Vishal; SETHI, Aman Preet Singh; KUMAR, Khushmeet (Walailak Journal of Science and Technology (WJST), 2013)
The finite element method (FEM) is a numerical analysis technique for obtaining approximate solutions to a wide variety of engineering problems. A finite element model of a problem gives a piecewise approximation to the governing equations. The basic premise of the FEM is that a solution region can be analytically modeled or approximated by replacing it with an assemblage of discrete elements (discretization). Since these elements can be put together in a variety of ways, they can be used to represent exceedingly complex shapes.